Religion in the interpretation of experience - Hofmeyr, Jan (Department of Religious Studies, 2023)
This dissertation initially grew out of a pre-occupation with the epistemological status of substantive religious beliefs. Its narrowly linguistic beginnings were soon broadened, however, for it became clear from the comparative study of religion that commitment to a tradition is an important part of discovering its veracity. In other words, it is through being linked in some way to the activities of a religious group that the truth of its doctrines is tested. This being so, the question of the epistemological status of substantive religious beliefs was seen to be linked to valuative considerations. The decision whether and in what way to be linked to the activities of a religious group in order to test its views is itself a valuative one. A pre-occupation with the epistemological status of religious beliefs gave way therefore to a more general pre-occupation with the relationship between value and "fact". At this point the investigation took what may be considered a peculiar turn for one concerned primarily with religion. It moved into the area of systems and information theory and into those areas of the human sciences in which an attempt is made to apply systems and information theoretic ideas, the reason being that the links between the way human beings value and the way they see the world seem to be most clearly conceived in these areas. Particularly significant is the extent to which it is becoming clear that human beings structure their "fact-gathering" in accordance with the informational requirements of goals. This does not mean that facts, in some sense or other, are value-laden, but only that the selection of facts will show valuative influences. While investigations influenced by systems and information concerns are clear on t~ relationship of information gathering to goal-directed activity, they are not however clear on the processes which may underlie the development of those goals. Since the predominant concern has been with the relationship between value and fact it became necessary to go beyond existing kinds of analysis to the development of a view of the way in which values underlie the acquisition of goals. This had the consequence ii of opening a way for the ideas generated in systems and information research to be app~ied to the interpretation of religion. Thus, the end product of a pre-occupation first with the epistemological status of substantive religious beliefs and second with the relationship between value and fact, was the development of a theory of religion i.e., of an account of the features in human nature which give rise to religion, and which make human beings religious at both individual and social levels. It is a highly speculative and theoretical account and, though some leads in this regard have been given in the texts and in footnotes, its application to religious studies in the field remains to be worked out. The body of the dissertation is divided into three sections. In the first the discipline of religious studies is introduced, and I argue for the importance of the development of an understanding of religion which traces it to at least a factor in human nature. Since this is an empirical problem, I set the study of human nature within what I consider to be its general scientific context. The systems approach to the study of human nature is then introduced, having been chosen for the clarity with which it links information gathering to goal-directed activity. This brings to a close the first section. The significance of the systems approach for understanding religion may not at this point be very clear. The purpose of the first section, however, is only to introduce that general approach to the . investigation and interpretation of religion which will follow. In the second section the theoretical underpinnings for the theory of religion are developed. A system of concepts in terms of which all human activity is shown to be value-based is defined and explained. It builds on the systems and information theoretic approach to the study of man but presses this approach further by the development of a scheme which links the acquisition of goals to underlying values. This opens the way to the application of these ideas to the interpretation of religion, a task carried out in the third section. In the third section a notion of what it is for an individual to be religious is developed in terms of the foundations laid in the first, and second sections. Religious activity is seen to arise out' of the operation in the individual of the valuing process at its most comprehensive. This understanding is then used to explore what the emergence of religion at a social level must involve. Since communication is so central to the operation of religion at a social level the dissertation comes full circle and links back to the preoccupation which was its initial stimulus i.e., that of the status of ~ substantive religious beliefs. This, however, is only one of the issues which it resolves. The value of the overall approach emerges by the clarity with which it links religious activity to other areas of human endeavour, religious experience to other areas of human experience, and religious discourse to other areas of human discourse. Throughout the dissertation use has been made of areas of thought in which many problems are still far from resolved. These areas, ·incomplete as they may be, have been pressed into service as providing the theoretical underpinnings of my view of religion. Clearly, there are critical intellectual dangers here for it might be argued that an attempt has been made to develop an understanding of religion on the basis of foundations which are still too insecure to support such an attempt. I have tried throughout, however, to leave the unresolved theoretical problems as open as they need to be for my final position to stand irrespective of _how they may be 'resolved. The predominant consideration in the adoption of an approach was the promise it held out for understanding religion. If it has been justified its justifiability will be shown therefore in its fruitfulness in the interpretation of religion, in its power to make interpretable that which has been but vaguely interpreted in the past.